Internationalization of Higher Education with Reference to the Arab Context: Proposed Model - Al-Atari, Aref Tawfiq Mohd Ali (IIUM Journal of Educational Studies, 2016)
This study aimed at articulating a model to put internationalization of higher education within the local and regional contexts. The model starts from theoretical premises inter alia: universities are established to advance knowledge which is by its very nature universal but they at the same time exist in nation states which have their own interests; nation states are not only entities of the world order but also parts of their regional orbit; and knowledge could be seen both as virtue sought for its own sake and as power and income generating good that is chased for utilitarian purposes. Expressed otherwise knowledge and education including higher education are not neutral but rather contested terrains. The question is how to be internationalized without being de-regionalized and de-nationalized (or de-contextualized). This is the thrust of this paper. Towards this purpose the author conducted a systematic review of related literature and models, articulated the points of departure and designed his own model. The author presented the proposed model and commented on it following the DDI modeling steps (Denoting, demonstrating and interpretation). The study ended with concluding remarks.